Society Response to Mobile Services on Mobile on The Road Investment Services and Integrated One-Stop Licensing Services in Tebing Tinggi City - Andy Akbar Perdana; Badaruddin Agus; Suriadi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
The aim of this study is to find out the society response Mobile Services on Mobile on The Road Investment Services and Integrated One-Stop Licensing Services in Tebing Tinggi City. This research was conducted at the Investment Office and the One-Door Licensing Service of Tebing Tinggi City. The result of this study The response given by every community that has taken care of business permits is also quite good, they feel satisfied that they have been well served by Mobile On The Road officers who are well served to arrive at the stage of delivering ready-made letters to them.